(untitled) (Dhaka Shishu (Children) Hospital Journal, 2026)
Background: Neonatal mortality remains a significant public health challenge, particularly in low- and middle-income countries like Bangladesh. Objective: This study aimed to analyze the patterns, predictors, and causes of neonatal mortality in a tertiary care hospital to inform targeted interventions. Methods: A retrospective cohort study was conducted at the Bangladesh Shishu Hospital & Institute, analyzing data from neonates admitted between August 1, 2022, and January 31, 2023. Key variables such as demographic details, time of death, duration of hospital stay, mode of delivery, and cause of death were examined using descriptive statistics. Results: Of the 1,418 neonates admitted during the study period, 91 (6.42%) experienced mortality. A slightly higher proportion of deaths occurred among male neonates (52.75%) compared to females (47.25%). The highest incidence of mortality was observed during nighttime hours (42.86%), and nearly half of the deaths (48.35%) occurred within the first 24 hours of admission. More than half of the neonates who died were delivered via cesarean section (53.85%), and the majority were born in hospitals (75.82%). The leading causes of death were preterm low birth weight and its complications (28.57%), neonatal sepsis (26.37%), and birth asphyxia (24.18%). Conclusion: The study identified preterm low birth weight, sepsis, and birth asphyxia as the primary causes of neonatal mortality, with a high rate of early mortality and a higher prevalence of nighttime deaths. These findings suggest the need for improved perinatal care, better infection control, and enhanced monitoring, especially during critical periods. DS (Child) H J 2024; 40(1): 5-11